2011
DOI: 10.1111/j.2041-210x.2011.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for non‐independent detection when estimating abundance of organisms with a Bayesian approach

Abstract: Summary1. Binomial mixture models use repeated count data to estimate abundance. They are becoming increasingly popular because they provide a simple and cost-effective way to account for imperfect detection. However, these models assume that individuals are detected independently of each other. This assumption may often be violated in the field. For instance, manatees (Trichechus manatus latirostris) may surface in turbid water (i.e. become available for detection during aerial surveys) in a correlated manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 13 publications
6
130
1
Order By: Relevance
“…This can lead to overinflation of counts and contrasts with the approach taken in distance sampling [21], which models the detectability of groups of individuals. However, a beta-binomial distribution can be applied to address nonindependence of detections of individuals [52,53].…”
Section: Reviewmentioning
confidence: 99%
“…This can lead to overinflation of counts and contrasts with the approach taken in distance sampling [21], which models the detectability of groups of individuals. However, a beta-binomial distribution can be applied to address nonindependence of detections of individuals [52,53].…”
Section: Reviewmentioning
confidence: 99%
“…As a remedy to this problem, Martin et al (2011) proposed an observation model wherein the beta distribution was used to specify random variation in detection probabilities among surveys. For example, suppose detection probability varies among repeated surveys of the same location and the source of variation cannot be measured.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite our efforts to mitigate for individual heterogeneity, the maximum per-cell abundance estimates from the hair trap-only analysis of males were unrealistically high (N = 150 in one cell). Other research [22] found that when detection of individuals is correlated, which could result from non-independent movement of animals, abundances were overestimated. Although it is unknown whether other forms of individual heterogeneity yield inflated abundance estimates, it seems likely that other forms of individual heterogeneity remain within our hair trap-only sample for males.…”
Section: Discussionmentioning
confidence: 96%